2019
DOI: 10.1051/matecconf/201926907003
|View full text |Cite
|
Sign up to set email alerts
|

Initial Study for Cerium and Lanthanum Extraction from Bangka Tin Slag through NaOH and HClO4 Leaching

Abstract: The global demand for rare earth elements have increased dramatically for the last decade as more and more devices use rare earth elements as key for their advanced properties. The paper explores the possibilty to recover cerium (Ce) and lanthanum (La) in Bangka tin slag (BTS) involving roasting at 900°C, water-quenching, and two leachings, 8M NaOH leaching and HClO4 leaching at concentrations of 0.1M, 0.4M, and 0.8M. HClO4 leaching causes Ce and La contents to decrease to 0.47% for 0.1M, 0.51% for 0.4M, and 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Thus, 30 % of the impurities in the concentrate, including REE, were also smelted and became slag. The first smelting slag still contained 20-30 % of Sn and was smelted again to obtain slag with only 2-3 % Sn content [12]. This second smelting slag, later called Bangka Tin Slag (BTS), was used in this study.…”
Section: Pre-treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, 30 % of the impurities in the concentrate, including REE, were also smelted and became slag. The first smelting slag still contained 20-30 % of Sn and was smelted again to obtain slag with only 2-3 % Sn content [12]. This second smelting slag, later called Bangka Tin Slag (BTS), was used in this study.…”
Section: Pre-treatmentmentioning
confidence: 99%
“…In tantalum and niobium extraction from tin slag, studies that have been carried out reveal several alternative processes, including leaching with H 2 SO 4 and HF, decomposition of slag with NaOH at high temperatures, or a combination of acid-base leaching. The reaction of silica with sodium hydroxide resulted in sodium silicate (Na 2 SiO 3 ) which is soluble in water [12]. REE, including Ce contained in slag, was assumed to be in the form of hydroxide after going through an alkaline fusion process.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Modification of TiO 2 catalyst by doping ions mechanism using the rare earth materials proven can enhance the photocatalytic activity [18]. Cerium (Ce) is one of the attractive rare earth materials that could prevent the electron-hole recombination rate in TiO 2 [19,20]. The study reported that doping of Ce up to 1 % (w/w) in TiO 2 can increase the photocatalytic efficiency in the 4-chlorophenol dye to be optimum up to 86.6 % for 3h at doping of 0.6 % Ce.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%